1999
DOI: 10.1007/s004649901129
|View full text |Cite
|
Sign up to set email alerts
|

Laparoscopic cholecystectomy and gallbladder cancer

Abstract: Thickened and infiltrated gallbladder walls in patients without preoperative symptoms of cholecystitis should raise a suspicion of cancer. The surgeon should be prepared to perform a conversion, an intraoperative histological examination, and an appropriate radical operation, if necessary.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
21
1

Year Published

2000
2000
2015
2015

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 12 publications
0
21
1
Order By: Relevance
“…This procedure is also advised by other authors [7,15,23]. Wyscocki et al [30] recommend conversion to an open resection prior to removal.…”
Section: Discussionmentioning
confidence: 91%
“…This procedure is also advised by other authors [7,15,23]. Wyscocki et al [30] recommend conversion to an open resection prior to removal.…”
Section: Discussionmentioning
confidence: 91%
“…In a 1978 report, gallbladder cancer was an incidental finding in <1% of patients undergoing cholecystectomy [8]. In a more recent study of laparoscopic cholecystectomy, only six cases of cancer (0.29%) were found among 2,017 patients [13]. However, the incidence of carcinoma of the gallbladder among patients presenting with acute cholecystitis has not been well studied.…”
Section: Discussionmentioning
confidence: 97%
“…It has been reported that GBC is detected in approximately 1% of patients undergoing cholecystectomy5 and that GBC is unexpectedly found in 0.2%–0.8% of patients undergoing LC . As increasing numbers of LCs are being performed, its role in the management of potentially malignant disease must be carefully examined.…”
Section: Discussionmentioning
confidence: 99%